2017
DOI: 10.1523/jneurosci.3389-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Malat1 Regulates Cerebrovascular Pathologies in Ischemic Stroke

Abstract: The study was designed to determine the role of long noncoding RNA (lncRNA), metastasis-associated lung adenocarcinoma transcript 1 (Malat1), in ischemic stroke outcome. Primary mouse brain microvascular endothelial cells (BMECs) were cultured and treated with Malat1 GapmeR before 16 h oxygen and glucose depravation (OGD). Cell death was assayed by LDH and MTT methods. Malat1 knock-out and wild-type mice were subjected to 1 h of middle cerebral artery occlusion (MCAO) and 24 -72 h of reperfusion. To explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
218
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(224 citation statements)
references
References 39 publications
6
218
0
Order By: Relevance
“…Overall, these results reveal that up regulation of MALAT1 exerts its biological roles through regulation of MDM2 expression in ischemic stroke. A previous study indicated that Malat1 plays anti-apoptotic and anti-inflammatory roles in the brain microvasculature to reduce ischemic stroke [7]. In addition, studies have uncovered the regulation pattern of Malat1 expression mediated by p53 in hematopoietic differentiation [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results reveal that up regulation of MALAT1 exerts its biological roles through regulation of MDM2 expression in ischemic stroke. A previous study indicated that Malat1 plays anti-apoptotic and anti-inflammatory roles in the brain microvasculature to reduce ischemic stroke [7]. In addition, studies have uncovered the regulation pattern of Malat1 expression mediated by p53 in hematopoietic differentiation [26].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are potential novel biomarkers that should be explored further for use in the diagnosis, treatment and prognosis of stroke [6]. Metastasisassociated lung adenocarcinoma transcript 1 (MALAT1) is a highly abundant lncRNA that exerts anti-inflammatory and anti-apoptotic roles in the brain microvasculature to reduce ischemia in the cerebral vasculature [7]. Studies have shown that MALAT1 regulates the function of endothelial cells and vessel growth [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In HeLa cells, it has been shown to control the HIF-1α axis under hypoxic conditions in a positive feedback loop [20]. After ische­mic stroke, it regulates gene expression in cerebrovascular endothelial cells [21, 22], where it is proposed to protect against hypoxia-reperfusion-induced apoptosis [23]. MALAT1 has been of interest as a therapeutic target after its downregulation was found to suppress ischemic injury and autophagy in vitro and in vivo, which makes its strong upregulation in our data of particular interest [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work points to the role of lncRNAs in oligodendrocyte precursor cell (OPC) differentiation from neural stem cells (NSCs), myelination and remyelination in the CNS [29, 30]. lncRNA (Malat1) displays anti–apoptotic and anti-inflammatory roles in microvasculature structure of the brain to reduce ischemic brain injury [31]. However, there is a large gap between the number of existing lncRNAs and their known association with a particular molecular or cellular function in MS/EAE.…”
Section: Discussionmentioning
confidence: 99%